Development Of Floor Exercies Learning Module assisted By A Quick Response Code For Eight Grade Students Of Public Junior High School Number Five Lubuklinggau - Wawan Syafutra; Rico Juliansa (Universitas Muhammadiyah Enrekang, 2022)
The research aime toproduce a floor gymnastics learning module assisted by a quick response code for class eight grade students that is valid and practicial. This research is a development research using the ADDIE model. This model consists of five stages, namely the analysis stage (analysis), the planning stage (Design), the development stage (Developing), and evaluation (evaluation). Data collection techniques in the research used interviews, observations, and questio,nnaeeires. The data analysis technique used the validty steps of linguist getting a score of0,80, material expert getting a score 0,89, and media expert getting a score of 0,90 base on the result of the analysis of the three experts, namely linguists, material expert, and experts the media showa that the floor excercies learning module with q quick response code has met the valid criteria. Furthermore, the practicial analysis teacher and of small group stundents got a score of 83,72% so the practicality of the floor excercies learning module assisted by a quick response code for the eight class student of SMP Negeri 5 Lubuklinggau was Categorized as vary strong in practicalitiy. So it can be concluded the the floor gymanastics learning module assited by a quick response code has met the b=valid and practicial and can be used in learning.